Identification of Neisseria meningitidis by MALDI-TOF MS may not be reliable. (June 2019) - Hong, E.; Bakhalek, Y.; Taha, M.-K.
Abstract: Objectives: The matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) technique is increasingly used in hospital laboratories for routine identification of microorganisms. However, its performance is variable, particularly for highly variable species such as Neisseria meningitidis . Reliable identification of N . meningitidis is crucial for the management of invasive meningococcal disease by rapid implementation of treatment and preventive measures among close contacts. We assessed and improved N . meningitidis identification by MALDI-TOF MS by enriching the databases with reference strains identified using whole genome sequencing (WGS) as a reference standard. Methods: We first built a collection of 24 strains from several species of the Neisseria genus that we characterized by WGS. This collection was added to the available database to test by MALDI-TOF MS another collection of 32 clinical isolates received between 2015 and 2017 at the French National Reference Laboratory for Meningococci. Results: Using the commercially available library of mass spectrometry profiles, only 67% (95% confidence interval (CI), 47–82) concordance was observed at the species level between MALDI-TOF MS and WGS characterization. However, when the new enriched reference collection was used on the second subset of isolates, the identification of N . meningitidis was significantly improved (p 0.0016), showing 92% (95% CI, 75–98) specificity while that of the manufacturer's database alone was 52% (95% CI, 34–70). Conclusions: Our data highlight the need to update the available MALDI-TOF MS database with high-quality references to enhance the identification of N . meningitidis and avoid unwarranted preventive measures or missing identification.